2022
DOI: 10.1111/jopr.13602
|View full text |Cite
|
Sign up to set email alerts
|

Polyetheretherketone computer‐aided design and computer‐aided manufacturing framework for All‐on‐Four mandibular full‐arch prosthesis: 3 Years' retrospective study of peri‐implant soft tissue changes and ridge base relationship

Abstract: Purpose This study was conducted to evaluate the clinical peri‐implant soft tissue changes during the first year after occlusal loading and the ridge base relation after 3 years for mandibular computer‐aided design and computer‐aided manufacturing (CAD‐CAM) screw‐retained implant‐supported hybrid prosthesis of polyetheretherketone (PEEK) framework utilized with All‐on‐Four treatment concept. Materials and methods Sixteen completely edentulous patients were rehabilitated by four implants following the All‐on‐Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Despite that some studies mentioned that implant number has no influence on the soft tissue in implant supported overdenture cases, the All-on-Four treatment concept was established to intensify the use of existing remnant bone in atrophic jaws, which permits instant function and evades regenerative procedures (15) (16) . Adding to that an efficient prosthetic basis can be established from the well-spread implants (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Despite that some studies mentioned that implant number has no influence on the soft tissue in implant supported overdenture cases, the All-on-Four treatment concept was established to intensify the use of existing remnant bone in atrophic jaws, which permits instant function and evades regenerative procedures (15) (16) . Adding to that an efficient prosthetic basis can be established from the well-spread implants (17) .…”
Section: Discussionmentioning
confidence: 99%
“…All four patients with biological complications presented history of periodontitis or smoking habits, representing risk indicators for the incidence of biological complications [44,45]. The good results registered for these outcome measures (implant survival, marginal bone loss and biological complications) can be potentially attributable to PEEK's properties, specifically its shock absorption characteristics [9,10,[46][47][48]. Recent finite element analysis studies reported conflicting results when evaluating PEEK infrastructures used in full-arch implant-supported rehabilitations and the ad modum All-on-4 concept: Tribst et al [24], Ersöz et al [26], Yu et al [27] and Dayan et al [28] reported that PEEK frameworks transferred more stress to the bone in both compression and tensile stress compared to other metallic frameworks (including titanium) in what could be perceived as placing the rehabilitations at an increased risk of biological complications.…”
Section: Discussionmentioning
confidence: 99%
“…The use of alternative materials for implant-supported rehabilitations is the object of constant development. One such alternative is polyetheretherketone (PEEK), a highperformance thermoplastic polymer whose application was extended from the aerospace and automotive industry [1] to medicine [2][3][4] and dentistry [5][6][7][8][9][10][11][12], either alone or reinforced with polymer composite materials [13,14]. Given its original development (Victrex plc, Lancashire, UK), the properties that make PEEK an exciting alternative include creep and wear resistance, biostability, biocompatibility, superior mechanical behavior, and compatibility with medical diagnostic imaging [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible application of PEEK is for the production of post-and-core restorations and occlusal splints [75]. Glass fiber-reinforced PEEK provides excellent mechanical properties, shear bond strength, and biocompatibility when used for post-and-core restorations according to Zhao et al [76].…”
Section: Peekmentioning
confidence: 99%